2021
DOI: 10.1111/cei.13646
|View full text |Cite
|
Sign up to set email alerts
|

CD4+LAG-3+ T cells are decreased in active psoriatic arthritis patients and their restorationin vitrois mediated by TNF inhibitors

Abstract: Psoriatic arthritis (PsA) is a chronic inflammatory disease associated with T cell dysregulation. The lymphocyte-activation gene (LAG)-3 is one of the regulatory receptors expressed on T cells in a soluble form. LAG-3 expression on T cells was analyzed in vitro in PsA patients with minimal disease activity (MDA), active disease (non-MDA) and healthy controls. In cultured in-vitro peripheral blood mononuclear cells (PBMCs), LAG-3 expression on CD4 + T cells was similar in both MDA PsA patients (7.5 ± 0.9) (n = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…A previous study revealed an inverse association between the PASI score and the level of CD4+CD49b+LAG-3+Type 1 Tregs in the blood of patients with psoriasis (53). Reduced LAG-3 levels were also found in patients with PsA (54). For psoriasis, the production of interferon (IFN)a by plasmacytoid DCs is the initial event in the innate cascade to pathologic inflammation.…”
Section: Role Of Lag-3 In Psoriasismentioning
confidence: 99%
“…A previous study revealed an inverse association between the PASI score and the level of CD4+CD49b+LAG-3+Type 1 Tregs in the blood of patients with psoriasis (53). Reduced LAG-3 levels were also found in patients with PsA (54). For psoriasis, the production of interferon (IFN)a by plasmacytoid DCs is the initial event in the innate cascade to pathologic inflammation.…”
Section: Role Of Lag-3 In Psoriasismentioning
confidence: 99%
“…was associated with impaired levels of lymphocyte-activation gene (LAG)-3 receptor expression on CD4 + lymphocytes. The authors also noted TNF inhibitors (TNFi) could up-regulate CD4-LAG-3+ levels, with possible improvement on the control of disease activity (12). Considering that phosphodiesterase 4 (PDE4) could be involved in the cleavage of the soluble form of CD40L (sCD40L), a second study by Venerito et al investigated the effect of Apremilast (APR), a PDE4 inhibitor, on sCD40L levels and PsA activity.…”
Section: Pathogenesismentioning
confidence: 99%